Amphiboles and Other Hydrous Pyriboles Mineralogy - Ribbe, Paul H.; Veblen, David R. (Reviews in Mineralogy & Geochemistry, 2018)
Most of Volume 9A of Reviews in Mineralogy treats amphiboles and other hydrous pyriboles as isolated systems. It reviews the structural complexity and resulting chemical variability and diversity of petrologic behavior of amphiboles, whereby Volume 9A contains a hefty dose of petrology and in contrast, Volume 9B is dedicated more to an exploration of the social life of amphiboles and the amphibole personality in real rocks and in the experimental petrology laboratory. This volume was prepared in conjunction with the Mineralogical Society of America Short Course on Amphiboles and Other Hydrous Pyriboles, Fall, 1981.